Theoretic-Methodolodical and Technological Basic of the Directed Development of the Educational Systems - Osadchyi, Ivan (Pedagogical Discourse, 2015)
The theoretic-methodological and technological principles of the directed development of the educational systems are disclosed. The definition «directed development» of the educational systems as the process of their changing according to the selected direction, determined content and duration was defined and put into the scientific circulation. The use of the directed development of the educational systems as an effective mechanism of the reformation was grounded. It is found out that theoretic-methodological principles of the directed development of the educational systems are initial positions and derivative consequences of theory WB-systems («systems without boundary»). It is proved that the purposeful distribution of that or other order on local, module or general-system levels is provided by the development and the realization of separate administrative actions as innovative, having special purpose projects as carriers of this order or their concerted totalities – cascade programs of development. It was found out that it is expedient to use the technology of project-target management development of the educational systems as a means of providing directed development of the educational systems.